Environmental governance towards microplastic pollution : the case of personal care and cosmetics products in Bangladesh - Islam, Shariful (2019)
Recent years have seen increased attention of academics, practitioners and policymakers regarding microplastic pollution, which is posing a severe threat to ecosystems and human health. Microbeads, a subset of microplastics, are intentionally added to personal care and cosmetics products (PCCPs). Many countries in the global North have already banned the use of microbeads in PCCPs. The literature, however, has largely overlooked microplastic pollution and governance intervention against the use of plastic microbeads in PCCPs in developing countries. This paper attempts to fill this gap by taking Bangladesh as an example, where evidence of microbead pollution has recently been discovered. The purpose of this study is to increase understanding of the perceptions, views and recommendations of policymakers and other stakeholders about microplastic pollution from microbead-containing PCCPs in Bangladesh and related gov-ernance and policy intervention. This exploratory study uses qualitative research method and collects primary data through semi-structured interviews of 12 key in-formants, comprising relevant government officials, industry representatives, academia and civil society actors in Bangladesh. The theoretical framework for this study has been drawn from governance and policy literature. The collected data has been transcribed and analyzed using qualitative content analysis. The findings suggest that the awareness of microbead pollution among policymakers and other stakeholders is low, but attitude towards microbead use is quite strong, many asking for bans. The findings put forward some interesting drivers and barriers perceived by the participants in policy making and implementation against microbead use.